Brief Report: European Mitochondrial Haplogroups Impact on Liver Fibrosis Progression Among HCV and HIV/HCV-Coinfected Patients From Northwest Spain. (1st October 2016) - Tabernilla, Andres; Rego-Pérez, Ignacio; Grandal, Marta; Pernas, Berta; Pértega, Sonia; Delgado, Manuel; Mariño, Ana; Álvarez, Hortensia; Mena, Alvaro; Rodríguez-Osorio, Iria; Pedreira, Jose Domingo; Blanco, Francisco Javier; et al.
Abstract : Abstract: The impact of mitochondrial DNA haplogroups on the outcome of liver fibrosis was evaluated in 362 hepatitis C virus infection (HCV)-monoinfected and HIV/HCV-coinfected patients (147 and 215, respectively) in clinical follow-up at 2 reference hospitals in the Northwest of Spain. The mitochondrial DNA haplogroup H was the most prevalent (50.3%) in this population. The cluster Others and V were recognized as risk factors for the development of liver fibrosis while haplogroup H and HCV genotype 4 confer a lower risk. This information might be useful for prioritization of HCV treatment, especially for F0-F1 patients for whom there is no urgency for treatment.